Penerapan Model Project Based Learning Pada Peserta Didik Kelas IV Tema 3 Peduli Terhadap Lingkungan Hidup Sub Tema 2 Keberagaman Makhluk Hidup di Lingkunganku di SDN Sawunggaling VIII/389 Surabaya - Rizabati, Balak Betari (Universitas PGRI Adi Buana Surabaya, 2017)
The using 2013 curriculum made some of some changing based on the learning process in the school. to push the student's ability in order to create the contextual creation, individual or group so more suggested using the learning approach which is created the creation of problem-solving basic (project-based learning). so that way the researcher applied (Project Based Learning) on care theme to be live creatures subtheme the various are live creatures in my environment learning 1. the purpose of this research is (1) describe the teachers' ability on manage the learning during use project-based learning, (2) describe the students' activities on project-based learning (3) describe the result of combination between the project task assessment and the result learning on care theme to be live creatures subtheme the various are live creatures in my environment learning 1 fourth grade SDN Sawunggaling VIII/389 Surabaya. This research used quantitative research design with use the precentage of descriptive quantitative method. the population in this research are all the students of fourth grade that amoung 76 students, and the sample in this research is IV-A grade that amoung 39 students. the collection data technique used the observation and test. the instrument research used the THB validation, RPP, observation sheet, and THB student's sheet. the analysis data technique used validity test, presentage descriptive which is continued with average test the result of this research is all about teacher's ability is belong to good criteria (SB), to students' activities is belong to very good criteria (B) and good (B) because the amount the students that do phase activities project based learning is higher than the students do not. and to combination the project task assesment and learning result test, is all about got the value (B+) with the presentage is about 62% and good criteria (B) on attitude competency with the presentage is about 72%. with the classical pass, grade is about 100%. The conclusion of this research is the application Project based learning model on care theme to be live creatures subtheme the various are live creatures in my environment learning 1 fourth grade SDN Sawunggaling VIII/389 Surabaya is called effective.